Quantitative analysis of the gaze and the kinetic/kinematic evaluation of expert and novice physical therapists during standing/sitting assistance: a pilot study - Satoru Sekine; Satoru Sekine; Yoshimi Sakurai; Yoshimi Sakurai; Yoshitsugu Omori; Yoshitsugu Omori; Yuji Morio; Yuji Morio; Junichi Yamamoto (Frontiers Media S.A., 2024)
IntroductionIn rehabilitation practices, expert therapists are believed to proficiently observe and assist patients. However, limited research has quantified the gaze behaviors of physical therapists during patient support. This study investigated the gaze patterns of expert and novice physical therapists from a first-person perspective during the process of assisting collaborators to stand. The aim was to determine which body parts received prolonged attention and to explore the characteristics of the support provided.MethodsSeven experienced physical therapists were recruited as expert participants, and 17 physical therapy students served as novice participants. We also recruited additional students as collaborators and asked them to behave as if they were patients. Both expert and novice participants wore a wearable eye tracker while assisting the collaborators to stand. We analyzed the gaze focus on specific body parts and the center of mass sway of the collaborators.ResultsExperts spent 10.75% of the total time gazing at the head area, compared to 4.06% for novices, with experts displaying significantly longer gaze durations (p < .05). Furthermore, there was a significant difference in the number of gaze fixations, with experts averaging 25.71 fixations and novices 8.65 (p < .05). Experts also facilitated a slower sway in the collaborator's center of mass (0.44 m/s for experts vs. 0.49 m/s for novices; p < .01) and positioned the collaborator with a more pronounced trunk flexion during sitting and standing transitions (41.0 degrees for experts vs. 37.8 degrees for novices; p < .01).DiscussionThe findings suggest that experts may monitor the collaborator's center of mass position by focusing on the head area. Properly positioning the head forward may allow for optimal forward movement of the center of mass, potentially reducing the effort required by the collaborator to stand. This study is the first to explore differences in support strategies through the measurement of physical therapists' gaze during assistance.